Penerapan Metode Inquiry-Based Learning Dalam Upaya Peningkatan Hasil Belajar Matematika Tentang Himpunan - Sungkono Sungkono (Unisda Journal of Mathematics and Computer Science (UJMC), 2020)
In mathematics learning especially in the material of assemblies in class VII-B MTs Negeri 2 Mojokerto in the 2018/2019 academic year, there are many obstacles. The lack of students' ability to understand the set material can be seen from the results of initial observations by the researcher. The subject of this research are 37 students consisting of 9 boys and 28 girls, the initial student abilities were identified as follows: (a) very good of 7 people or 18.92%; (b) either of 7 people or 18.92%; (c) sufficient of 5 people or 13.51%; (d) less of 13 people or 35.14%; and (e) very less of 5 people or 13.51%. This research applied the inquiry-based learning method to improve mathematics learning outcomes. This research was conducted with a classroom action research design with two cycles. Based on the results and discussion, it was concluded that student learning outcomes before using the inquiry-based learning method were categorized as poor with a percentage of 59.56%. After using the inquiry-based learning method in learning, there was an increase in learning outcomes in a good category, reaching 75.80% in cycle I, and an increase in cycle II reaching a percentage of 83.40%. The level of student learning success in cycle I was 80.67%, increasing to 86.13% in cycle II.